The role of supplementary feeding sites in vulture conservation in South Africa - Brink, Christiaan Willem (Department of Biological Sciences, 2022)
Supplementary feeding is a management application often used to support declining wildlife populations or facilitate reintroductions. Nowhere is it perhaps more popular, than in vulture conservation. Vulture supplementary feeding sites (SFS), also known as vulture restaurants, are specific locations where carcasses and unwanted animal parts are provided for vultures to feed on. This is proposed to be a win-win scenario in that contributors to the site receive a free carcass disposal service while simultaneously supporting vulture populations. SFS are assumed to benefit vultures through enhancing demographic parameters such as breeding success and survival. While there is some evidence for such effects, more recent critical assessments are questioning assumptions that these effects are ubiquitous. Additionally, research has begun to identify unintended negative consequences to both target and non-target species and the larger ecosystem. SFS may consequently be counterproductive to conservation goals in some cases. Most of these critical assessments have been conducted in Europe, and southern Africa, the supposed birthplace of SFS, remains understudied. In light of the ongoing African vulture crisis, which has seen vulture populations plummet across the continent, effective investment of conservation resources is critical in preventing the extinction of this functional group. The main aim of this thesis was therefore to evaluate what role SFS play in vulture conservation in a southern African context. I specifically focus on South Africa, where SFS is widespread and have a long history. To understand the value of SFS I needed to verify the proposed positive effects of this conservation measure and assess any potential negative consequences of the practice. First, this required base-line information on the scale and extent of the practice. Secondly management practices and the motivations of managers needed to be reviewed to understand the context in which these sites function and whether there are any risks to vultures using these sites. Thirdly, the distribution of the major threat to vultures (i.e., poisoned carcasses), which SFS are proposed to mitigate, needed to be determined. And finally, the presumed positive effect of SFS on vultures needed to be tested. I could then examine the potential trade-offs of this management practice. In this thesis I first describe the distribution and contribution of SFS to vultures at a national level. I do this by compiling records and databases from various organisations involved in vulture conservation. Then, using a snow-ball survey method and telephonic and email interviews, I verify the activity and history of all recorded and newly discovered SFS. Using this method, I identify 143 currently active SFS across the country, feeding an average of 64.6 kg per day. Overall provisioning at SFS amounted to an estimated 3301 tonnes of food per year. An amount equivalent to 83% of the food requirements of all vultures in the region. I show that different vulture species have varying access to this resource depending on their range. Food provisioning was highly skewed to only 17% of SFS which are providing 69% of the food. Consequently, species with smaller home ranges have relatively poor access to food provided at SFS when compared to further ranging species. In this first chapter, I provide the necessary base-line information that has previously hampered the critical assessment of the effects of this intervention. Using information from the survey conducted with SFS managers I then investigate the context in which these SFS function and their adherence to best management practices. Half of the SFS surveyed were associated with livestock farming and the majority were private individuals not officially affiliated with any conservation organisation. The pervasive sentiment under managers is that SFS are beneficial (84% of managers) and most managers are unable to indicate any disadvantages to themselves in the running of SFS. The cleaning service provided by the vultures is the most widespread perceived benefit. While managers may receive benefits from this practice, I show that their low awareness of vulture conservation issues may lead to practices that are harmful to vultures. For example, despite experts identifying unintentional and intentional poisoning from poison laced carcasses as the most critical threats to vultures, only 47 and 24% of managers, respectively, listed these as potential threats to vultures. Additionally, while most managers (85%) assess carcasses for provisioning suitability based on whether they had been treated with veterinary drugs, relatively few managers (10%) did the same for lead (Pb) contamination. Worryingly, only 30% of managers consider threats to vultures, such as the proximity of power lines, when deciding on a location for their SFS. Overall, current management practices are not adequate to guarantee the safety of vultures using SFS. I therefore advise that increased awareness and training is required and perhaps more stringent guidelines and regulation of the practice. As I show a correlation between the numbers of vultures seen at SFS and the amount of food provided there, the initial focus for such training and regulation should be the SFS with the highest provisioning rates. More formal regulation of this practices will also allow for its targeted application in relation to threats in the landscape. To inform such management and to control for the major cause of vulture declines in subsequent analysis, I investigate the prevalence and motivations for using poison as a predator control method under livestock farmers. I do this via face-to-face surveys using a specialised questioning technique and ad hoc quantitative methods. This reveals that an estimated 22% and 31% of farmers use poison over a 1-year and 5-year period, respectively. Poison use hotspots generally coincide with small stock farming areas and the strongest predictor for its use is its perceived prevalence under peers. My results, however, indicate that farmers are less likely to use poisons if they frequently encounter vultures on their farm. The widespread positive attitude displayed towards vultures along with the other findings provide leverage points to change behaviours and mitigate this threat. In addition to the proposition that SFS mitigate the threat from poison laced carcasses, they are also proposed to assist breeding vultures and increase their success in raising young. To test this, I use monitoring data on South African Cape vulture colonies spanning over two decades, to model the effects of SFS on breeding success, while accounting for threats such as poison use and the provisioning of Pb contaminated food. I also test whether Pb contaminated food potentially proved at SFS is affecting breeding success. I show that the amount of food provided annually at SFS is weakly positively associated with breeding success, but that these results are not significant. I find that a reduced proximity of SFS to vulture colonies is negatively associated with breeding success, but this result is also not significant. Lastly, I find no evidence that the amount of potentially Pb contaminated food provided at SFS, nor the average prevalence of carcass poisoning in the area, affected local breeding success. These results cast doubt on the current dominant narrative in the conservation sphere, which asserts that SFS have positive effects on vulture demographic parameters, such as breeding success. In this thesis, I show that some a priori assumptions about the benefits of SFS in vulture conservation may be overvalued and unjustified. Furthermore, I uncover that current management practices may be endangering vultures feeding at these sites, the problem of which is heightened by the identified widespread use and level of provisioning occurring at a landscape scale. It is therefore an urgent matter to examine other effects, both positive and negative, that SFS have on vultures and the rest of the ecosystem. In this thesis I have provided the necessary information to conduct such research. Until a net benefit to vultures is shown a refocussing of conservation efforts on directly combatting the major causes of vulture declines may be warranted to ensure the effective spending of limited conservation resources.